Physical and Mental Health of Children with Developmental Coordination Disorder - Caçola, Priscila (Frontiers in Public Health, 2016)
Developmental coordination disorder (DCD) is a neurodevelopmental condition characterized by poor motor proficiency that interferes with an individual’s activities of daily living. These problems in motor coordination are prevalent despite children’s intelligence levels. Common symptoms include marked delays in achieving motor milestones and clumsiness, typically associated with poor balance, coordination, and especially handwriting skills. Currently, DCD is said to impact about 2–7% of school-age children. More importantly, DCD is considered to be one of the major health problems among school-aged children worldwide, with unique consequences to physical and mental health. Because these children and adolescents often experience difficulties participating in typical childhood activities (e.g., riding a bike), they tend to be more sedentary, more overweight/obese, at a higher risk for coronary vascular disease, and have lower cardiorespiratory and physical fitness than their typically developing peers. From another perspective, the motor difficulties have also been linked to an increased risk for mental health issues, such as higher anxiety and depression. The understanding of the health consequences associated with DCD offers practical applications for the understanding of the mechanisms and intervention protocols that can improve the consequences of this condition. In this review, I will explore such consequences and provide evidence for the implementation of interventions that focus on improving physical and mental health in this population.